2005
DOI: 10.1002/mrd.20310
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the major proteins of ram seminal plasma

Abstract: Mammalian seminal plasma contains among others, two major families of proteins, namely spermadhesins and those proteins that contain fibronectin type II domains. Spermadhesins are the major proteins of boar and stallion seminal plasma and homologous proteins have been identified in the bull. These proteins appear to be involved in capacitation and sperm-egg interaction. In bovine seminal plasma, proteins containing fibronectin type II domains are the major proteins and are designated BSP proteins. These protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 48 publications
(47 reference statements)
10
81
0
6
Order By: Relevance
“…More recently (Barrios et al, 2005), we have proven that 2 proteins of approximately 14 (P14) and 20 (P20) kDa are responsible for this protective and restoring effect. By cytochemical analysis, we showed that both proteins have several binding sites on the sperm surface, and the NH 2 -terminal sequencing showed that the P14 fragment has a high homology with the bovine PDC-109 (Esch et al, 1983), GSP-14/15 kDa (goat seminal plasma protein, related to the BSP family) (Villemure et al, 2003), and the recently reported RSP15 of ram (Bergeron et al, 2005). The homology was found from amino acid 19-34 (CVFPFTYYDDRHFDCT) with 49-64 of PDC-109 (CVFPFVYRNRKHFDCT), which is the FN2 domain (Greube et al, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…More recently (Barrios et al, 2005), we have proven that 2 proteins of approximately 14 (P14) and 20 (P20) kDa are responsible for this protective and restoring effect. By cytochemical analysis, we showed that both proteins have several binding sites on the sperm surface, and the NH 2 -terminal sequencing showed that the P14 fragment has a high homology with the bovine PDC-109 (Esch et al, 1983), GSP-14/15 kDa (goat seminal plasma protein, related to the BSP family) (Villemure et al, 2003), and the recently reported RSP15 of ram (Bergeron et al, 2005). The homology was found from amino acid 19-34 (CVFPFTYYDDRHFDCT) with 49-64 of PDC-109 (CVFPFVYRNRKHFDCT), which is the FN2 domain (Greube et al, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…In addition to main immunoreactive fragments, low but detectable and distinct FN immunoreactivity of 8-15 kDa protein bands was observed. This pattern of low molecular mass species resembles that of the acidic gelatin-binding proteins as the main proteins present in the seminal plasma of different animals [21,[35][36][37]. As already mentioned, they contain an FN-type II domain, but there are no data on their possible antigenic relatedness with FN.…”
Section: Discussionmentioning
confidence: 79%
“…Our results mainly focusing on the 8 bands that are associated with fertility in south Indian Jersey and hybrid bulls. SDS-PAGE analysis of alcohol-precipitated ram seminal proteins indicated the presence of about 25 proteins with molecular masses from 14-120 kDa, a group of proteins with a molecular mass of 15-16 kDa and 22-24 kDa was more predominant (Bergeron et al, 2005). The relative content of protein for low fertility group and high fertility group of Jersey were found to be with significant different in that fertility associated proteins.…”
Section: Resultsmentioning
confidence: 90%